MENGOPTIMALKAN KINERJA PEGAWAI PERBANKAN SYARIAH MELALUI PENDEKATAN MOTIVASI KERJA KONTEMPORER - yulia harwina (Sekolah Tinggi Ilmu Ekonomi Riau, 2026)
Abstract : The purpose of this study was to determine the effect of work motivation on employee performance at PT. Bank Perkreditan Rakyat Syariah Pekanbaru. To achieve this goal, a study was conducted using a sample of 37 people, using the census method. The data analysis method used simple linear regression. Based on the results of the partial t-test, it was found that work motivation had a significant effect on employee performance at PT. Bank Perkreditan Rakyat Syariah Pekanbaru, this was proven based on the t-test, the calculated t was greater than the t-table (4.477> 2.035). The magnitude of the influence of the work motivation variable on the employee performance variable is 0.364 (36.4%). This is proven based on the results of the determination test where the R2 value is 0.364. The recommendation that can be submitted is expected that the relationship between superiors and subordinates can be strengthened again so that a harmonious relationship is established, because this received the lowest response from respondents.